Progress in Earth and Planetary Science - Tada, Ryuji; Iryu, Yasufumi; Ohtani, Eiji.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Progress in Earth and Planetary Science (PEPS), a peer-reviewed open access e-journal, was launched by the Japan Geoscience Union (JpGU) in 2014. This international journal is devoted to high-quality original articles, reviews and papers with full data attached in the research fields of space and planetary sciences, atmospheric and hydrospheric sciences, human geosciences, solid earth sciences, and biogeosciences. PEPS promotes excellent review articles and welcomes articles with electronic attachments including videos, animations, and large original data files. PEPS also encourages papers with full data attached: papers with full data attached are scientific articles that preserve the full detailed raw research data and metadata which were gathered in their preparation and make these data freely available to the research community for further analysis.
Keywords: Earth sciences; Geophysics; Planetary science; Biogeography; Geology; Atmospheric science; Earth Sciences; Geophysics; Planetary Science; Biogeosciences; Geology; Atmospheric Science